Toward Consensus on Correct Interpretation of Protein Binding in Plasma and Other Biological Matrices for COVID‐19 Therapeutic Development. Issue 1 (21st November 2020) - Boffito, Marta; Back, David J.; Flexner, Charles; Sjö, Peter; Blaschke, Terrence F.; Horby, Peter W.; Cattaneo, Dario; Acosta, Edward P.; Anderson, Peter; Owen, Andrew
Abstract : The urgent global public health need presented by severe acute respiratory syndrome‐coronavirus 2 (SARS‐CoV‐2) has brought scientists from diverse backgrounds together in an unprecedented international effort to rapidly identify interventions. There is a pressing need to apply clinical pharmacology principles and this has already been recognized by several other groups. However, one area that warrants additional specific consideration relates to plasma and tissue protein binding that broadly influences pharmacokinetics and pharmacodynamics. The principles of free drug theory have been forged and applied across drug development but are not currently being routinely applied for SARS‐CoV‐2 antiviral drugs. Consideration of protein binding is of critical importance to candidate selection but requires correct interpretation, in a drug‐specific manner, to avoid either underinterpretation or overinterpretation of its consequences. This paper represents a consensus from international researchers seeking to apply historical knowledge, which has underpinned highly successful antiviral drug development for other viruses, such as HIV and hepatitis C virus for decades.